Securing Messages by Using Coverless Steganography : A Survey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the last few decades, with the digitalization of information, digital data transmitted overinsecure communication can be under attack, so driving steganography to the forefront for securecommunication. Steganography is a method of transmitting hidden data via a suitable multimedia carrier. The fundamental issue of stenographic system design is to strike a reasonable balance between security, robustness, greater bit embedding rate, and imperceptibility. To send hidden communications over the internet, sophisticated steganography techniques are required. However, the object used to hide secret messages within may be exposed by compression or any form of noise, causing the secret message to be extracted erroneously. Therefore, non-traditional basics for information security, such as coverless image steganography, are necessary. Coverless image steganography does not need the usage of a cover image to embed the hidden data; rather it use its own intrinsic properties to do so. This paper includes contributions to provide a comprehensive survey in this field, where the essential frameworks, preprocessing, feature extraction, creation of hash sequences, and its mapping links have all been discussed, as well as a steganography overview of its primary types, categorization, and applications. Existing methodologies are examined, as well as future development opportunities.